PENERAPAN METODE WAIGHTED PRODUCT UNTUK MENENTUKAN TEMPAT STRATEGIS UNTUK BISNIS KULINER BERBASIS WEB (STUDI KASUS : KECAMATAN LEGOK) - Muhammad Saipudin Latif; Achmad Hindasyah (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Business is buying and selling activities with the aim of making a profit. Currently doing business has become an alternative to earn additional income besides the main job. Many things influence people to do business, one of which is a strategic location for doing business, both for beginners and those who want to expand their business. The problem faced by business people in determining a strategic location is not carefully considering the right location for doing business so that not a few survive because the location chosen is not strategic. Therefore we need a Decision Support system that can help business people to determine a strategic location to do business effectively. The method used in this study is the Waighted Product method. This method was chosen because it is able to select the best alternative from several alternatives considered, in this case the intended alternative is a strategic location based on predetermined criteria. Determining a strategic location is determined by determining the weight value for each criterion, then a ranking process is carried out which will determine the optimal alternative, namely a strategic location for doing business.